Overexpression of Efflux Pumps, Mutations in the Pumps’ Regulators, Chromosomal Mutations, and AAC(6′)-Ib-cr Are Associated With Fluoroquinolone Resistance in Diverse Sequence Types of Neonatal Septicaemic Acinetobacter baumannii: A 7-Year Single Center Study - Roy, Subhasree; Chatterjee, Somdatta; Bhattacharjee, Amrita; Chattopadhyay, Pinaki; Saha, Bijan; Dutta, Shanta; Basu, Sulagna (Frontiers in Microbiology, 2021)
This study investigates susceptibility towards three fluoroquinolones (ciprofloxacin, levofloxacin, moxifloxacin), multiple fluoroquinolone-resistance mechanisms and epidemiological relationship of neonatal septicaemic Acinetobacter baumannii. Previous studies on fluoroquinolone resistance in A. baumannii focused primarily on ciprofloxacin susceptibility and assessed a particular mechanism of resistance; a more holistic approach was taken here. Epidemiological relationship was evaluated by Multi Locus Sequence Typing. Minimum Inhibitory Concentrations of fluoroquinolones was determined with and without efflux pump inhibitors. Overexpression of efflux pumps, resistance-nodulation-cell-division (RND)-type and multidrug & toxic compound extrusion (MATE)-type efflux pumps were evaluated by reverse transcriptase-qPCR. Mutations within regulatory proteins (AdeRS, AdeN and AdeL) of RND-pumps were examined. Chromosomal mutations, presence of qnr & aac(6’)-Ib-cr were investigated. A. baumannii were highly diverse as 24 sequence-types with 6 novel STs (ST-1441/ST-1481/ST-1482/ST-1483/ST-1484/ST-1486) were identified among 47 A. baumannii. High resistance to ciprofloxacin (96%), levofloxacin (92%) and particularly moxifloxacin (90%) was observed, with multiple mechanisms being active. Resistance to 4th generation fluoroquinolone (moxifloxacin) in neonatal isolates is worrisome. Mutations within GyrA (S83L) and ParC (S80L) were detected in more than 90% of fluoroquinolone-resistant A. baumannii (FQRAB) spread across 10 different clonal complexes (CC1/CC2/CC10/CC25/CC32/CC126/CC149/CC216/CC218/CC513). Efflux-based FQ resistance was found in 65% of FQRAB with ≥2 different active pumps in 38% of strains. Overexpression of adeB was highest (2.2-34-folds) followed by adeJ, adeG, andabeM. Amino acid changes in the regulators (AdeRS/AdeN/AdeL) either as a single substitution or as combinations substantiated the overexpression of the pumps. Diverse mutations within AdeRS were detected among different CCs whereas mutations within AdeN linked to CC10 and CC32. Chromosomal mutations and active efflux pumps were detected simultaneously among 64% of FQRAB. Presence of aac6’Ib-cr was also high (74% of FQRAB) but qnrs were absent. As most FQRABs had chromosomal mutations this was considered predominant however isolates where pumps were also active had higher MIC values, establishing the critical role of the efflux pumps. The high variability of FQ susceptibility among FQRAB in spite of possessing the same set of mutations in gyrA, parC and efflux pump regulators was also noted. This reveals the complexity of interpreting the interplay of multiple resistance mechanisms in A. baumannii.